Status of Mathematics Teachers’ Espoused Beliefs about Nature and Teaching Learning Process of Mathematics - Tiwari, Dharma Datta (Mathematics Education Forum Chitwan, 2024)
This study aimed to investigate the espoused beliefs held by secondary-level mathematics teachers about mathematics and its teaching and learning processes. The research employed a quantitative survey design, focusing on four districts (Chitwan, Makawanpur, Gorkha, and Parsa) as representatives of Nepal. The selection of 168 mathematics teachers from these districts utilized proportional allocation of stratified random sampling. A questionnaire, employing a Likert five-point scale, was designed to collect data on teachers' espoused beliefs. The results revealed a prevalent alignment of secondary-level mathematics teachers' espoused beliefs with the fallibilist philosophy of mathematics. Additionally, the findings indicated a strong inclination towards the use of the constructivist method in teaching mathematics. This research contributes valuable insights into the prevailing beliefs among mathematics teachers at the secondary level, providing a basis for understanding their perspectives on the nature of mathematics and preferred teaching methodologies.